2013
DOI: 10.1164/rccm.201208-1530oc
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Prenatal Maternal Cortisol, Maternal Obesity, and Childhood Wheeze. Insights into Prenatal Programming

Abstract: Maternal prenatal cortisol disruption and obesity were independently associated with children's wheeze. Obese women with adverse cortisol profiles were most likely to have children with repeated wheeze.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 57 publications
4
60
0
Order By: Relevance
“…Of these, 14 studies with a total of 108 321 mother-child pairs were included in the meta-analysis [16][17][18][20][21][22][23][24][25][26][27][28][29][30] (Table 1). There was complete agreement on 469 of 474 articles after title and abstract screening (interreader agreement k = .90) and on 40 of 42 articles after full-text screening (k = .89).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 14 studies with a total of 108 321 mother-child pairs were included in the meta-analysis [16][17][18][20][21][22][23][24][25][26][27][28][29][30] (Table 1). There was complete agreement on 469 of 474 articles after title and abstract screening (interreader agreement k = .90) and on 40 of 42 articles after full-text screening (k = .89).…”
Section: Resultsmentioning
confidence: 99%
“…However, as with any meta-analysis, we were limited to the covariates available to us from the original articles. Finally, maternal obesity is also a risk factor for childhood obesity, and the elevated risk of asthma could result partly from the child's own obesity; however, such confounding is unlikely given that most of the included studies adjusted for birth weight 16,17,22,23,25,26,29,30 or for the child's weight or BMI at the time of assessment of the outcome. 17,23,25,27,29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together these studies suggest that abdominal obesity is a stronger predictor of asthma and that the effect is independent of the metabolic syndrome. Wright and colleagues investigated the link between maternal obesity and cortisol disruption on repeated childhood wheezing and showed that maternal obesity and cortisol disruption had independent influences on childhood wheezing in a cross-sectional analysis of pregnant mothers (14). Yet, a subgroup of obese mothers with adverse cortisol profiles characterized by abnormally elevated cortisol levels later in the day were most likely to have children with repeated wheeze.…”
Section: Obesitymentioning
confidence: 99%